Looking at people looking at art: observations of art interactions in an everyday urban environment - Knoll, Anna Lena; Mikuni, Jan; Specker, Eva (Frontiers in Psychology, 2025)
IntroductionPlacing art in urban spaces can make urban public environments more attractive and colorful by offering beautiful and restorative environments. This may invite people to spend time in the area and create opportunities for social engagement, and community development. In this observational study we collaborated with “Keine Galerie” (translating to “not a gallery”), a small window gallery in the city of Vienna (Austria) to address the following questions: Does the presence of publicly available art influence people's behavior (in terms of type, frequency, and duration) in an urban space? Does it enhance peoples' social interactions, such as the amount of conversations in a group?MethodsTo capture the impact of presence of art, we collected data during two exhibitions by two different artists at Keine Galerie (i.e., art conditions) as well as between exhibitions when no art was visible (i.e., control condition). We used observational methods to unobtrusively assess how pedestrians who were passing through the study area interact with their environment either with or without art.ResultsOur results showed that art being present invites passers-by to interact with the space more than when no art is present (no art vs. art conditions) but also that the type of art may matter (Ex.1 vs. Ex. 2), which influenced not just the amount of interactions but also which interactions took place.DiscussionWe discuss these quantitative and qualitative differences, also with regard to potential confounding factors (e.g., weather), and propose avenues for further research into the impact of art in public space.